Numerical Study of the Medicane of November 2014 - Pytharoulis, I.; Matsangouras, Ioannis T; Tegoulias, I.; Kotsopoulos, S; Karacostas, Theodore S.; Nastos, P. T. (PERSPECTIVES ON ATMOSPHERIC SCIENCES, 2016)
{A hurricane-like cyclone with an `eye', eyewall convection and strong winds affected central Mediterranean basin on 7-8 November 2014. The maximum observed sustained wind speed was 22 m/s (tropical storm strength) at Lampedusa. Significant damages were reported from this island and the coastal regions of eastern Sicily. Thus, it is essential to study medicanes and calibrate the numerical weather prediction models in order to simulate them adequately. Operational ECMWF analyses are used together with the non-hydrostatic Weather Research and Forecasting numerical model with the Advanced Research dynamic solver (WRF-ARW ver 3.7.1). The aims of this study are to simulate the system and investigate the sensitivity of the model on the microphysical scheme, the number of vertical levels and the global input dataset. The main characteristics of the medicane are represented in good agreement with observations and analyses, but, no single setup is able to provide the best reproduction of all its features.}